The treatment strategies for spine fractures in patients with ankylosing spondylitis: A case report. Issue 44 (November 2017) - Zhu, RuSen; Song, WenYe; Hu, Wei; Jiang, ZeHua; Yuan, JianJun; Cui, ZiJian; Wan, Jun; Liu, Yan; Feng, ShiQing; Zhang, XueLi
Abstract: Purpose: The aim of the study was to explore surgical strategies for effectively treating spine fractures in patients with ankylosing spondylitis (AS) and investigate the postoperative outcomes. Methods: We retrospectively analyzed 9 patients with AS that was complicated by spine fractures, who underwent surgery at our spine and spinal cord clinic between 2005 and 2012. The surgical methods included posterior instrumentation and bone grafting, with or without decompression. Fracture healing and neurological function recovery were observed postoperatively. The average follow-up period was 45.1 months (range: 24–60). Results: The 9 patients included 7 men and 2 women. Eight patients were treated with long posterior fixation. One patient underwent combined long posterior fixation and anterior bone grafting. The neurological function of these patients improved significantly to varying degrees after surgery, and fracture union and segmental instability of the lumbar vertebrae were radiologically confirmed at the 1-month and 2-year follow-up intervals. Severe surgery-related complications were not observed. Conclusions: Posterior instrumentation with bone grafting was a satisfying method for treating spine fractures in patients with AS.